Energy-Efficient Scientific Workflow Scheduling Algorithm in Cloud Environment. (14th March 2022) - Garg, Neha; Neeraj,; Raj, Manish; Gupta, Indrajeet; Kumar, Vinay; Sinha, G. R.
Abstract : Scheduling extensive scientific applications that are deadline-aware (usually referred to as workflow) is a difficult task. This research provides a virtual machine (VM) placement and scheduling approach for effectively scheduling process tasks in the cloud environment while maintaining dependency and deadline constraints. The suggested model's aim is to reduce the application's energy consumption and total execution time while taking into account dependency and deadline limitations. To select the VM for the tasks and dynamically deploy/undeploy the VM on the hosts based on the jobs' requirements, an energy-efficient VM placement (EVMP) algorithm is presented. Demonstrate that the proposed approach outperforms the existing PESVMC (power-efficient scheduling and VM consolidation) algorithm.